Effect of Light-Activated Hypocrellin B on the Growth and Membrane Permeability of Gram-Negative Escherichia coli Cells - Yuan Jiang; Wingnang Leung; Qingjuan Tang; Hongwei Zhang; Chuanshan Xu (International Journal of Photoenergy)
Aim. To investigate the effect of light-activated hypocrellin B on the growth and membrane permeability of Gram-negative bacteria. Methods. Escherichia coli (E. coli) as a model bacterium of Gram-negative bacteria was incubated with various concentrations of hypocrellin B for 60 min and was subsequently irradiated by blue light with wavelength of 470 nm at the dose of 12 J/cm2. Colony forming units were counted and the growth inhibition rate of E. coli cells was calculated after light-activated hypocrellin B. Membrane permeability was measured using flow cytometry and confocal laser scanning microscopy (CLSM) with propidium iodide (PI) staining. Bacterial morphology was observed using transmission electron microscopy (TEM). Reactive oxygen species in bacterial cells were measured using flow cytometry with DCFH-DA staining. Results. Significant growth inhibition rate of E. coli cells was observed after photodynamic action of hypocrellin B. Remarkable damage to the ultrastructure of E. coli was also observed by TEM. Flow cytometry and CLSM observation showed that light-activated hypocrellin B markedly increased membrane permeability of E. coli. Flow cytometry showed the intracellular ROS increase in E. coli treated by photodynamic action of hypocrellin B. Conclusion. Light-activated hypocrellin B caused intracellular ROS increase and structural damages and inhibited the growth of Gram-negative E. coli cells.